Olfactory processing and odor specificity: a meta-analysis of menstrual cycle variation in olfactory sensitivity - Martinec Nováková, Lenka; Havlíček, Jan; Roberts, S. Craig (Anthropological Review, 2014)
Cycle-correlated variation in olfactory threshold, with women becoming more sensitive to odors mid-cycle, is somewhat supported by the literature but the evidence is not entirely consistent, with several studies finding no, or mixed, effects. It has been argued that cyclic shifts in olfactory threshold might be limited to odors relevant to the mating context. We aimed to test whether the evidence currently available points in the direction of odor-specific or, rather, general changes in olfactory sensitivity and, if the former is the case, to what group of odorants in particular. We carried out a meta-analysis of relevant studies which together used a variety of different odorants, including some found in food, body odor, and some that occur in neither of these. First we tested whether there appears to be an overall effect when all studies are included. Next, we hypothesised that if cyclic changes in olfactory processing are odor-specific and tuned to biologically relevant odors, we should find changes in detection thresholds only for odorants found in body odor, or for those that are perceptually similar to it. In contrast, if threshold patterns are linked to more general fluctuations in odor processing across the cycle, we would not expect changes in relation to any particular odorant group. The results support the view that there is significant cycle-correlated variation. Thresholds were in general significantly lower in the fertile than the non-fertile phases, with effect sizes consistently in this direction. This same conclusion applied to both ‘food’ and ‘musky’ odorants, despite their different evolutionary significance, and to the androgen steroids (androstadienone, androstenone, and androsterone), but could not be applied to phenyl-ethyl alcohol. The results indicate that olfactory sensitivity may be a non-adaptive by-product of the general physiological fluctuations or differences in neural processing experienced across the cycle to a broad spectrum of odorants, rather than being specifically selected for mate choice-related odors.